Mengkaji Asal ½ dari Rumus Luas Segitiga dalam Pemaparan oleh Guru kepada Siswa - Mustika, Tito Nur; Ismiasih, Novi (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
The area of a triangle is a basic concept in geometry that has wide applications in various fields, ranging from pure mathematics to applied sciences such as engineering and architecture. An understanding of how to calculate the area of a triangle is essential for solving various problems involving area measurement and calculation. The basic formula for calculating the area of a triangle is half the product of the base and the height (½ × base × height). The teacher's teaching of the proof of the triangle area formula at school, there are some things that create ambiguity in the explanation. Usually the teacher in explaining the origin of ½ of the triangle area formula starts from a square or rectangle that is divided on its diagonal plane, then makes ½ part of the square or rectangle area only. Whereas it can come from other rectangular or quadrilateral planes, which include: square, rectangle, parallelogram, kite, rhombus, trapezium. The formation of ½ in the triangle area formula comes from the ratio equation of total angles and area between triangles and quadrilaterals. So, with the concept ratio equation of total angles and area between triangles and quadrilaterals, students can understand that all quadrilateral flat shapes can be used to find the triangle area formula